The interaction between actin and FA fragment of diphtheria toxin - Ünlü, A. (Springer Netherlands, 2012)
Actin protein has many other cellular functions such as movement, chemotaxis, secretion and cytodiaresis. Besides, it have structural function. Actin is a motor protein that it has an important role in the movement process of toxin in the cell. It is known that F-actin gives carriage support during the endosomal process. Actin is found in globular (G) and filamentous (F) structure in the cell. The helix of actin occurs as a result of polymerisation of monomeric G-actin molecules through sequential rowing, is called F-actin (FA). Actin interacts with a great number of cellular proteins along with cell skeleton and plasma membrane. It is also known that some bacterial toxins have ADP-ribosylation affect on actin. Diphteria toxin is the part which has the FA enzymatic activity corresponding the N-terminal section of the toxin, which inhibits the protein synthesis by ADP-ribosylating the elongation factor 2 in the presence of NAD. FA, taken into the cell by endocytosis inhibits protein synthesis by ADP-ribosyltransferase activity and breaks the cytoskeleton. In the studies both in vitro and in vivo, actin with interaction FA of diphteria toxin has been yet to be fully elucidated. The aim of this study was to determine the three dimensional structures of actin with interaction FA of diphteria toxin by the amprical methods and in paralel with the computing technology, theoretical methods have gained significant importance. In our study, actin with interaction FA of diphteria toxin has been determined as the most possible interaction area with the theoretical method; analogy modelling. This area has been closed in the presence of polypeptides and FA-actin interactions have been tested with the gel filtration chromatography techniques. As a result of the findings, we found that 15 amino acid artificial peptides (DAMYETMAQACAGNR) corresponding to 201–215 amino acid residues of FA interacts with G-actin and closes this area. Secondly, in the model formed with the analogy modelling, it appears that the most possible interaction area is between FA (tyr204) and G-actin (gly48). Results obtained from both theoretical and experimental data support the idea that the interaction occurs in this area.